Playing to win how strategy really works - Lafley, A.G. (Alan G.) (Harvard Business Review Press, 2013)
Strategy = choice -- What is winning? -- Where to play -- How to win -- Playing to your strengths -- Managing what matters -- Thinking through strategy -- Shortening your odds.